H/F substituted perovskite compounds with above-room-temperature ferroelasticity: [(CH3)4P][Cd(SCN)3] and [(CH3)3PCH2F][Cd(SCN)3]. Issue 58 (1st July 2019) - Cao, Ying-Jie; Zhou, Lin; Shi, Ping-Ping; Ye, Qiong; Fu, Da-Wei
Abstract : [(CH3 )4 P][Cd(SCN)3 ] and its fluorine-substituted product [(CH3 )3 PCH2 F][Cd(SCN)3 ] perfectly demonstrate the new concept of fluorine substitution, maintaining ferroelasticity while increasing dielectric properties. Abstract : An organic–inorganic perovskite compound [(CH3 )4 P][Cd(SCN)3 ] (1 ) and its fluorine-substituted product [(CH3 )3 PCH2 F][Cd(SCN)3 ] (2 ) exhibit ferroelastic phase transitions above room temperature. The very close van der Waals radii of H and F atoms ensure isomorphism of the crystal structures. However, the higher phase transition temperature, stronger ferroelastic spontaneous strain value and dielectric properties of2 can possibly be explained by differences in the electronegativity between F and H atoms.